Organophosphate induced delayed neuropathy in genetically dissimilar chickens: Studies with tri-ortho-cresyl phosphate (TOCP) and trichlorfon - Honorato de Oliveira, Georgino [UNESP]; Moreira, Vanessa [UNESP]; Ribeiro Goes, Sheila Patricia [UNESP] (Elsevier, 2002)
Measurements of plasma cholinesterase (pl.ChE), brain cholinesterase (Br.ChE) and brain Neuropathy Target Esterase (Br.NTE) were made in three different lineages of chickens. All birds received toxicants through gavage in a single oral dose between 08:00 and 09:00 h, after overnight fast. Babcock chickens were treated with 800 mg/kg tri-ortho-cresyl phosphate (TOCP) or 80 mg/kg trichlorfon. The TOCP group had 82% Br.NTE inhibition, when compared to the control group, and no birds displayed symptoms of clinical organophosphate-induced delayed neuropathy (OPIDN). Hy-line w36 lineage chickens were given 1600 mg/kg TOCP and despite this higher dose, Br.NTE inhibition was similar that presented by Babcock chickens. Isabrown chickens were given 1600 mg/kg TOCP or 80 mg/kg trichlorfon. At 36 h all trichlorfon treated birds had from 80 to 90% inhibition of Pl.ChE and Br.ChE, when compared to controls. However, Br.NTE was inhibited less than 20%, and there were no clinical signs of OPIDN. All TOCP treated isabrown chickens had more than 80% Br.NTE inhibition while one of them exhibited just light signs of OPIDN, two chickens became totally paralyzed. This finding suggested that chicken strain was important in the appearance of OPIDN. In addition, 70-80% of NTE inhibition was necessary but was not sufficient to produce OPIDN in chickens, since babcock and hy-line w36 chickens exhibited NTE inhibition in the range of 70-80% without clinical signs of OPIDN. © 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Chicken strain; Cholinesterase; Neurotoxic target esterase; Organophosphate induced delayed neuropathy; Tri-ortho-cresyl-phosphate; Trichlorfon; cholinesterase; metrifonate; neurotoxic esterase; organophosphate; tri ortho cresyl phosphate; animal experiment; animal model; animal tissue; brain level; chicken; cholinesterase blood level; clinical feature; controlled study; dose response; enzyme inhibition; feeding; genetic difference; line difference; neuropathy; nonhuman; organophosphate induced delayed neuropathy; paralysis; priority journal; symptom; Animals; Brain; Carboxylic Ester Hydrolases; Central Nervous System Diseases; Chickens; Cholinesterases; Insecticides; Time Factors; Tritolyl Phosphates; Aves; Gallus gallus